Purification and Charcterization of Pectinesterase from Potato - Abbas, Ayat Adnan (Al-Nahrain Journal of Science, 2018)
Pectin esterase was extracted from potato and determining its activity were investigated. Crude enzyme recorded specific activity 25.18 U / mg and increasing specific activity of the enzyme after dialysis concetraion recording 107.14 U/ mg, then the enzyme peak after using anion ion-exchange chromatography was recorded a specific activity reached 192.31 U /mg and fold of the purification 8.2 and yield 23.34%, either gel filtration was the fold of the purification 19.8times and with specific activity 476. 28 U / mg with the proceeds of 50. 68%. The optimum pH of the pure enzyme was 7.0 and optimum temperature was 50°C, while the stability of the pH of the pure enzyme was pH 8.0 and temperature stability at 60°C.